Índice de Sustentabilidad Ambiental de los GAD’s del Ecuador, 2012. - Carrión Robles, Daniela Caroley (2015)
This research order degree aims to build an index for Environmental Sustainability for GAD's of Ecuador, for 2012, from an economic, social, environmental and institutional perspective. To develop general aspects are described basically concepts related to sustainability, origin and evolution regarding the Constitution of the Republic of Ecuador, the Organic Law of Municipalities, municipal ordinances, Environmental Management Act besides its roles and Responsibilities as a tool to achieve sustainability. Research shows the process followed to design the Environmental Sustainability Index of GAD's of Ecuador and validated through a series of variables and indicators weighted and standardized, so they can be comparable with the global sustainable rate. Finally, the research concludes with the importance of creating the index of environmental sustainability, since it provides a baseline on the status of environmental economic reality of GAD's, allowing classify municipalities according to the grading scale in sustainable, moderately sustainable, municipalities having low sustainability and municipalities that do not have any degree of sustainability, which serves as a reference for policy makers in these areas making decisions.